Respuesta :
Answer:
20
Step-by-step explanation:
-3y+12=-48 1) Subtract 12 from both sides
1) -3y+12=-48
-12 -12
2) -3y=-60 2) Divide both sides by -3
-3 -3
3) y=20
-3y+12=-48
Move 12 to the other side of the equation by subtracting and cancelling out 12
-3y=-36
Then divide by -3 to both sides to get Y by itself
Y=12
A Negative multiplied by a negative equals a positive.
Move 12 to the other side of the equation by subtracting and cancelling out 12
-3y=-36
Then divide by -3 to both sides to get Y by itself
Y=12
A Negative multiplied by a negative equals a positive.